2016
DOI: 10.1063/1.4972867
|View full text |Cite
|
Sign up to set email alerts
|

Cu-metalated carbyne acting as a promising molecular wire

Abstract: Cu-metalated carbyne acting as a promising molecular wire The atomic structure and electronic transport properties of Cu-metalated carbyne are investigated by using the non-equilibrium Green's function formalism combined with density functional theory. Our calculations show that the incorporation of Cu atom in carbyne improves its robustness against Peierls distortion, thus to make Cu-metalated carbyne behave as a one-dimensional metal. When a finite Cu-metalated carbyne chain is connected to two (111)-oriente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…For each Cu-carbyne chain in 3-CuCR, the C�C bonds exhibit torus-shaped IRI-π isosurfaces, maintaining the intrinsic double π (π in and π out ) interaction features. 31,32 Besides, the weak single π interactions exist for C−Cu−C bonds, where the torus-shaped IRI-π isosurfaces near Cu atoms may arise from the 3d xz /d yz orbital, which initially exists in the individual Cucarbyne chain 33 (see Figure S5). In the cross-chain regions, the IRI-π isosurfaces between the C�C bonds are localized in the middle of the adjacent Cu-carbyne chains, indicating a weak face-to-face π−π stacking interaction, similar to the aromatic− aromatic interaction with sandwich configuration, which maximizes the overlap of π systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For each Cu-carbyne chain in 3-CuCR, the C�C bonds exhibit torus-shaped IRI-π isosurfaces, maintaining the intrinsic double π (π in and π out ) interaction features. 31,32 Besides, the weak single π interactions exist for C−Cu−C bonds, where the torus-shaped IRI-π isosurfaces near Cu atoms may arise from the 3d xz /d yz orbital, which initially exists in the individual Cucarbyne chain 33 (see Figure S5). In the cross-chain regions, the IRI-π isosurfaces between the C�C bonds are localized in the middle of the adjacent Cu-carbyne chains, indicating a weak face-to-face π−π stacking interaction, similar to the aromatic− aromatic interaction with sandwich configuration, which maximizes the overlap of π systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The isosurface and color-filled maps of the IRI function for the π molecular orbitals of 3-CuCR, referred to as IRI-π, are shown in Figure c,d to further reveal the interchain interactions. For each Cu-carbyne chain in 3-CuCR, the CC bonds exhibit torus-shaped IRI-π isosurfaces, maintaining the intrinsic double π (π in and π out ) interaction features. , Besides, the weak single π interactions exist for C–Cu–C bonds, where the torus-shaped IRI-π isosurfaces near Cu atoms may arise from the 3d xz /d yz orbital, which initially exists in the individual Cu-carbyne chain (see Figure S5). In the cross-chain regions, the IRI-π isosurfaces between the CC bonds are localized in the middle of the adjacent…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CuC 2 was recently synthetised 100 as a result of metalation of carbon chains from ethyne precursors on the Cu(110) surface in ultrahigh vacuum conditions, and the finite metalated chain was proposed as a promising molecular wire. 101 Notably, here we found that the material is exfoliable starting from multiple 3D van der Waals crystals, making the production potentially simpler. In particular, it can be extracted from three compounds of the family of experimentally known ternary alkali-metal carbides: NaCuC 2 , KCuC 2 , and RbCuC 2 102,103 (Figure 4); our calculations show that it can be exfoliated from KCuC 2 with a moderate binding energy of 636 meV/Å, comparable with that of known quasi-1D materials like αtellurium (376 meV/Å) and Sb 2 S 3 (528 meV/Å).…”
Section: Resultsmentioning
confidence: 77%
“…More importantly, in 2012, researchers found that metal elements could effectively modulate the electrical properties of GDY, which included the redistribution of electron orbitals and the efficient electron transfer between metal and GDY caused by a strong coupling effect. , Beyond that, density functional theory (DFT) calculations also prove that the structure of −CC–metal–CC– can significantly improve GDY electronic properties, which jointly show that the metallization engineering is an effective strategy for further enhancing the catalytic performance. Meantime, the GDY with naturally distributed cavity structures and rich carbon atoms displays a high affinity with metal atoms. Therefore, metalated-GDY has drawn increasing interest. However, the research on the efficient synthesis of metalated GDY is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%